SPECIALIZED EDUCATIONAL SERVICE AND EVERYDAY LIFE AT SCHOOL: ‘PARTNERSHIP AND CONFLICTS’ - Magalhães Araújo, Ana Cristina; Wendel Santana Coêlho, Márcio (Revista Gênero e Interdisciplinaridade, 2022)
The present article proposes to investigate the daily relationships in the pedagogical work developed between the Common Class and the Specialized Educational Assistance (SEA) in the daily life of a school in the municipal network of Elementary School I. It analyzes the legal attributions of the actors involved, the partnerships developed and possible existing conflicts in the researched field. The study consists of a qualitative approach and literature review to support the analysis of the interviews. The bibliographic study is based on national legislation and the concepts of Mantoan (2010), Ropoli (2010), Machado (2013), Smith (2008), Baptista (2011), among others. Finally, the results indicate that there are no frequent relational conflicts in the articulation of AEE with common education, and the relationship is established in collaborative work, exchange of knowledge and mutual respect, to solve problem situations present in everyday school life.